2022
DOI: 10.1038/s41598-022-05826-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche modeling predicting the potential distribution of African horse sickness virus from 2020 to 2060

Abstract: African horse sickness is a vector-borne, non-contagious and highly infectious disease of equines caused by African horse sickness viruses (AHSv) that mainly affect horses. The occurrence of the disease causes huge economic impacts because of its high fatality rate, trade ban and disease control costs. In the planning of vectors and vector-borne diseases like AHS, the application of Ecological niche models (ENM) used an enormous contribution in precisely delineating the suitable habitats of the vector. We deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…However, due to multicollinearity, these variables could not all be included in the model. Multicollinearity checks were performed on 26 environmental variables which were verified using the VIF procedure of the USDM package in R software 20 . Variables with Pearson correlation coefficient greater than 0.7 and VIF values greater than 8 were excluded from the variable set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to multicollinearity, these variables could not all be included in the model. Multicollinearity checks were performed on 26 environmental variables which were verified using the VIF procedure of the USDM package in R software 20 . Variables with Pearson correlation coefficient greater than 0.7 and VIF values greater than 8 were excluded from the variable set.…”
Section: Methodsmentioning
confidence: 99%
“…CA has been incorporated in the ensemble modeling approach. First, it could be used to predict a suitable niche model, and second, it could also be used to evaluate the performance of the model 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Ecological niche models of AHS and BTV have typically incorporated projections of temperature alongside multiple other environmental variables. One study has identified South America, the Indian subcontinent, and Australia as being the most suitable areas for AHS in future climates (Assefa et al 2022) and another suggested BTV will broaden in central Africa, the United States, and western Russia (Guis et al 2012).…”
Section: Climatementioning
confidence: 99%
“…Beyond climatic factors, land cover and altitude are also instrumental in understanding the spread of AHS (17, 32, 33). These elements contribute to the creation of suitable habitats for vectors, thereby influencing the distribution and intensity of AHS outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these diverse environmental influences (17, 33, 41), our study aims to integrate these varied environmental factors into a cohesive model. By employing a global-scale approach and focusing on variable identification, we endeavor to elucidate the general laws governing the spread of AHS and address the geographical variability in prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%